1989
DOI: 10.2527/jas1989.673835x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Methionine for Ruminants: Relative Bioavailability of Zinc in Lambs and Effects of Growth and Performance of Growing Heifers

Abstract: Studies were conducted to evaluate zinc methionine (ZnMet) as a source of Zn for ruminants. Experiment 1 compared the availability of Zn in ZnMet and zinc oxide (ZnO) in lambs fed a semi-purified diet deficient in Zn. Based on growth rate and animal performance, plasma Zn and plasma alkaline phosphatase activity, no differences in Zn availability were detected between the two Zn sources. Apparent absorption of Zn also was similar, but Zn retention was higher (P less than .01) in lambs fed ZnMet because of a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
124
2
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 15 publications
13
124
2
5
Order By: Relevance
“…Apparent absorption and retention of zinc in lambs which obtained organic forms were higher in comparison to animals received this trace element as oxide. On the contrary, Spears (1989) in experiments on fattening lambs indicated that apparent absorption of zinc from zinc-methionine and oxide was similar. However, the zinc excretion in urine was lower for lambs which received zinc-methionine, what caused the increase of zinc retention.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Apparent absorption and retention of zinc in lambs which obtained organic forms were higher in comparison to animals received this trace element as oxide. On the contrary, Spears (1989) in experiments on fattening lambs indicated that apparent absorption of zinc from zinc-methionine and oxide was similar. However, the zinc excretion in urine was lower for lambs which received zinc-methionine, what caused the increase of zinc retention.…”
Section: Discussionmentioning
confidence: 93%
“…The higher content of zinc in blood serum lambs and cows after application of organic forms of this element (bioplexes) in comparison with inorganic source of zinc indicated Kinal et al (2003Kinal et al ( , 2005aKinal et al ( ,2005b and Strusińska et al (2003). On the other hand, Spears (1989) had not indicated the influence of zinc form (Zn-methionine vs. zinc oxide) in lambs on its level in blood serum. As Spears (1989) stated the increase of zinc amount in tissues with application of organic forms of this element did not depend only on zinc source but also on zinc level in ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace minerals are generally supplemented in the animal diet as inorganic salts. However, in recent years, chelated or organic minerals are being used as the bioavailability of these minerals is more than their inorganic counterparts (Spears, 1989). Lambs supplemented with zinc proteinate had higher Zn retention than lambs given a similar concentration of Zn from zinc oxide, an inorganic source (Lardy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In four consecutive studies conducted by [30], Zn was better retained when added as Zn methionine than ZnO in lambs and heifers. However, the observed improvement was not due to higher absorption but to a lower urinary Zn excretion in animals receiving Zn methionine, and only minor changes in blood parameters were noticed.…”
Section: Zinc Availability From Organic and Inorganic Sourcesmentioning
confidence: 99%